Understanding China : a guide to China's economy, history, and political culture - Starr, John Bryan (New York : Hill and Wang, 2010)
In this succinct, modest, and refreshingly forthright book--now revised and updated for the new century--Starr introduces to the uninitiated reader the background, basic data, and issues at stake in China's crisis-ridden present and future. The death of Deng Xioaping in February 1997, revelations about Chinese influence in our election campaigns, and Chinese eagerness to acquire advanced American technology, are only some of the developments that show how urgently we need to know and understand China better than we do. In this revised edition of his essential book, Starr focuses his shrewd attention on them all. He furnishes additional material on China's relations with Taiwan and Tibet, the transfer of Hong Kong to Chinese rule, China's nuclear weapons program, and its environmental and human rights records. --
Includes bibliographical references and index.
Keywords: China -- Politics and government -- 1976-2002.; China -- Politics and government -- 2002-; China -- Economic conditions -- 1976-2000.; China -- Economic conditions -- 2000-